Evaluation of a Novel Pulsatile Extracorporeal Life Support System Synchronized to the Cardiac Cycle: Effect of Rhythm Changes on Hemodynamic Performance. Issue 1 (January 2015) - Patel, Sunil; Wang, Shigang; Pauliks, Linda; Chang, Dennis; Clark, Joseph B.; Kunselman, Allen R.; Ündar, Akif
Abstract Arrhythmias are a frequent complication during extracorporeal life support (ECLS). A new ECLS system can provide pulsatile flow synchronized to the patient's intrinsic cardiac cycle based upon the R wave of the electrocardiogram (ECG). It is unclear how the occurrence of arrhythmias may alter the hemodynamic performance of the system. This in vitro study evaluated the effect of simulated arrhythmias on hemodynamics during R wave‐triggered pulsatile ECLS. The ECLS circuit with an i‐cor diagonal pump and iLA membrane ventilator was primed with whole blood at room temperature. Flow and pressure data were collected at 2.5 and 4 L/min for each condition using a customized data acquisition system. Pulsatile ECLS flow was R wave synchronized to an ECG simulator using 1:1, 1:2, and 1:3 assist ratios. Conditions tested included sinus rhythm at 45 and 90 bpm, supraventricular tachycardia (SVT), ventricular tachycardia (VT), and irregular rhythms such as ventricular fibrillation. Pulsatile mode was successfully triggered by ECG signals of normal sinus rhythm, SVT, VT, atrial fibrillation, atrial flutter, and ventricular bigeminy with assist ratios 1:1, 1:2, and 1:3. Regular rhythm at 90 bpm generated the best surplus hemodynamic energy (SHE). For SVT and VT, an assist ratio of 1:2 resulted in maximum pulsatile flow waveforms with optimal SHE at 2.5 L/min flow rate. At 4 L/min, SHE declined and the pressure drop increased independent of arrhythmia condition. Irregular rhythms still produced adequate pulsatile wave forms at lower pulsatile frequency. This study demonstrated the feasibility of generating pulsatile ECLS flow with the novel ECG‐synchronized i‐cor system during various simulated rhythms. The optimal rate for pulsatile flow was 90 bpm. During irregular rhythms, the lower pulsatile frequency was the more reliable synchronization mode for generating pulsatile flow.